Predicting recessions with interest rate spreads: A multicountry regime-switching analysis - Ralf Ahrens (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
This study uses Markov-switching models to evaluate the informational content of the term structure as a predictor of recessions in eight OECD countries. The empirical results suggest that for all countries the term spread is sensibly modelled as a two-state regime-switching process. Moreover, our simple univariate model turns out to be a filter that transforms accurately term spread changes into turning point predictions. The term structure is confirmed to be a reliable recession indicator. However, the results of probit estimations show that the markov-switching filter does not significantly improve the forecasting ability of the spread. Klassifikation:
urn:nbn:de:hebis:30-9643
Keywords: E44; C22; C53; 330; term structure; economic fluctuations; forecasting; regime-switching